2006
DOI: 10.1152/ajpheart.00965.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acidic extracellular pH-activated outwardly rectifying chloride current in mammalian cardiac myocytes

Abstract: Yamamoto, Shintaro, and Tsuguhisa Ehara. Acidic extracellular pH-activated outwardly rectifying chloride current in mammalian cardiac myocytes. Am J Physiol Heart Circ Physiol 290: H1905-H1914, 2006. First published December 9, 2005 doi:10.1152/ajpheart.00965.2005.-Extracellular acidic pH was found to induce an outwardly rectifying Cl Ϫ current (ICl,acid) in mouse ventricular cells, with a half-maximal activation at pH 5.9. The current showed the permeability sequence for anions to be SCN Ϫ Ͼ Br Ϫ Ͼ I Ϫ Ͼ Cl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 26 publications
11
61
0
2
Order By: Relevance
“…The properties of ICl,pH in human keratinocytes are very similar to those reported in the above literatures; activation at pHe below 5.5 (room temperature), time-dependent kinetics, outward rectification, and high sensitivity to DIDS blocking (Nobles et al, 2004;Lambert et al, 2005;Yamamoto et al, 2006;Wang et al, 2007). In this respect, ICl,pH appears to be broadly expressed in mammalian cells, like volume-activated Cl current (ICl,vol).…”
Section: Acidic Ph-activated CL Currentssupporting
confidence: 82%
See 1 more Smart Citation
“…The properties of ICl,pH in human keratinocytes are very similar to those reported in the above literatures; activation at pHe below 5.5 (room temperature), time-dependent kinetics, outward rectification, and high sensitivity to DIDS blocking (Nobles et al, 2004;Lambert et al, 2005;Yamamoto et al, 2006;Wang et al, 2007). In this respect, ICl,pH appears to be broadly expressed in mammalian cells, like volume-activated Cl current (ICl,vol).…”
Section: Acidic Ph-activated CL Currentssupporting
confidence: 82%
“…The acidic pH-activated outward rectifying anion current similar to ICl,pH was firstly reported in rat Sertoli cells (Auzanneau et al, 2003) and subsequently in various types of cell lines (HEK-293, CHO, HeLa, PC-12, Caco-2 and HBE), hippocampal astrocytes and cardiac myocytes (Nobles et al, 2004;Lambert et al, 2005;Yamamoto et al, 2006;Wang et al, 2007). The properties of ICl,pH in human keratinocytes are very similar to those reported in the above literatures; activation at pHe below 5.5 (room temperature), time-dependent kinetics, outward rectification, and high sensitivity to DIDS blocking (Nobles et al, 2004;Lambert et al, 2005;Yamamoto et al, 2006;Wang et al, 2007).…”
Section: Acidic Ph-activated CL Currentsmentioning
confidence: 78%
“…These biophysical and pharmacological properties of neuronal acid-activated currents are phenotypically identical to those of ASOR anion channel expressing in a variety of non-neuronal cells. [1][2][3][4][5][6][7][8][9][10] Since our previous study 11 showed high sensitivity of the human epithelial ASOR channel currents to temperature, we next observed the effects of continuous changes in temperature of the extracellular solution from 22 to 38 °C on the mouse neuronal ASOR channel currents recorded at pH 5.25. The currents gradually decreased and increased with reducing and raising the temperature, respectively (Fig.…”
Section: Asor Anion Channel Is Expressed In Cortical Neurons and Is Tmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10] This channel is phenotypically characterized by activation by severe extracellular acidification alone as well as by strong outward rectification [1][2][3][4][5][6][7][8][9][10] and was shown to be involved in the genesis of acidotoxic necrotic cell death in human epithelial cells. 1 Our recent study 11 showed that the epithelial ASOR anion channel is sensitive to temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A novel Cl -current activated by extracellular acidosis (I Cl.acid ) has also been observed in cardiac myocytes but the molecular identity for I Cl.acid is currently not known (Yamamoto & Ehara, 2006).…”
Section: -Channels In the Heartmentioning
confidence: 99%